Radiotherapy, immunotherapy, and the tumour microenvironment: Turning an immunosuppressive milieu into a therapeutic opportunity. (1st April 2021) - Donlon, N.E.; Power, R.; Hayes, C.; Reynolds, J.V.; Lysaght, J.
Abstract: Immune checkpoint blockade (ICB) has revolutionised the treatment of solid tumours, yet most patients do not derive a clinical benefit. Resistance to ICB is often contingent on the tumour microenvironment (TME) and modulating aspects of this immunosuppressive milieu is a goal of combination treatment approaches. Radiation has been used for over a century in the management of cancer with more than half of all cancer patients receiving radiotherapy. Here, we outline the rationale behind combining radiotherapy with ICB, a potential synergy through mutually beneficial remodelling of the TME. We discuss the pleiotropic effects radiation has on the TME including immunogenic cell death, activation of cytosolic DNA sensors, remodelling the stroma and vasculature, and paradoxical infiltration of both anti-tumour and suppressive immune cell populations. These events depend on the radiation dose and fractionation and optimising these parameters will be key to develop safe and effective combination regimens. Finally, we highlight ongoing efforts that combine radiation, immunotherapy and inhibitors of DNA damage response, which can help achieve a favourable equilibrium between the immunogenic and tolerogenic effects of radiation on the immune microenvironment. Highlights: Radiotherapy exhibits immunogenic effects and has the potential to stimulate abscopal effects. The release of DAMPs is stimulated by radiotherapy resulting in immunogenic cell death. Radiotherapy upregulates signals in the TME promoting CD8 + T cell mediated killing. TME remodelling following radiotherapy depends on dose and fractionation. Hypofractionation with ICB demonstrates promising robust immunogenicity in preclinical studies.